Laser-optical diagnostics preclinical stage of periodontal diseases - S. P. Rubnikovich (Кубанский научный медицинский вестник, 2015)
The device for laser-optical diagnostics (LODdsf) in dentistry. The use LODdsf for the functional estimation of periodontal diseases is proved. Sensitivity and high information LODdsf provided an opportunity to evaluate differentiated initial preclinical stage of the inflammatory process in all topographic zones of the gums, which determined the timely assignment of corrective therapy.